2023
DOI: 10.1002/ana.26644
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neuronal Knockout of STAT3 Function Inhibits Epilepsy Progression, Improves Cognition, and Restores Dysregulated Gene Networks in a Temporal Lobe Epilepsy Model

Abstract: Objective Temporal lobe epilepsy (TLE) is a progressive disorder mediated by pathological changes in molecular cascades and hippocampal neural circuit remodeling that results in spontaneous seizures and cognitive dysfunction. Targeting these cascades may provide disease‐modifying treatments for TLE patients. Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) inhibitors have emerged as potential disease‐modifying therapies; a more detailed understanding of JAK/STAT participation in epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Network analysis placed STAT3 in the center of the Black GRN and immunofluorescence confirmed induction of STAT3 in neurons post SE. While activation of the JAK/STAT pathway in non-neuronal cells post-SE is well-characterized 26,47,61,62 , the role of STAT3 in neurons, especially in epilepsy has been less studied 45 . The mechanisms of neurogenic inflammation post-SE are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Network analysis placed STAT3 in the center of the Black GRN and immunofluorescence confirmed induction of STAT3 in neurons post SE. While activation of the JAK/STAT pathway in non-neuronal cells post-SE is well-characterized 26,47,61,62 , the role of STAT3 in neurons, especially in epilepsy has been less studied 45 . The mechanisms of neurogenic inflammation post-SE are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines released from glial cells following seizures increase neuronal excitability 66 , and type I IFNs increase excitability in neocortical pyramidal neurons via PKC 67 . Others have reported that seizure-induced activation of the JAK/STAT pathway reduces the number of gamma-aminobutyric acid (GABA) type A alpha1 receptors expressed in neurons following seizures, influencing GABA(A)R-dependent inhibition 27 ; this group has also utilized pharmacological inhibition of STAT3 32 and genetic ablation of the STAT3 SH2 domain 45 to reduce spontaneous seizure frequency in rodent models of epilepsy. In summary, activation of neuroinflammatory pathways, including the JAK/STAT pathway, has been shown to modulate neuronal excitability, and herein we identify EZH2 as a key negative regulator of the JAK/STAT pathway in epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 There is growing evidence suggesting that increased JAK/STAT activity also plays a role in epilepsy in both human and experimental settings (animal and cell/ organotypic culture models). [3][4][5][6] However, the precise contribution of this activity to epileptogenesis is still being established. The study by Tipton et al investigated the specific role of neuronal JAK/STAT3 function in epileptogenic processes, unprovoked seizure progression, and cognitive comorbidities in a mouse model of acquired temporal lobe epilepsy (TLE) generated by administration of intrahippocampal kainic acid (IHKA).…”
Section: Commentarymentioning
confidence: 99%
“…The study by Tipton et al investigated the specific role of neuronal JAK/STAT3 function in epileptogenic processes, unprovoked seizure progression, and cognitive comorbidities in a mouse model of acquired temporal lobe epilepsy (TLE) generated by administration of intrahippocampal kainic acid (IHKA). 3 Brain injury linked to events of traumatic brain injury, ischemia, and status epilepticus (SE) can trigger hyperactivation of the JAK/STAT pathway. 4,6,7 In a pilocarpine rat model of SE and acquired TLE, this group previously reported that suppression of the JAK/STAT signaling cascade with WP1066, a small molecule inhibitor of STAT3 signaling, given at the onset of SE resulted in a long-lasting reduction of spontaneous recurrent seizures (SRS).…”
Section: Commentarymentioning
confidence: 99%